ChemInform Abstract: 1, 4‐Addition Reaction of 5H‐Oxazol‐4‐ones to Allenic Esters and Ketones Catalyzed by Chiral Guanidines. Issue 46 (18th November 2014) - Jin, Nari; Misaki, Tomonori; Sugimura, Takashi
Abstract Title reaction of 2‐halophenyl‐substituted 5H‐oxazol‐4‐ones [(I) or (V), resp.] provides adducts [(III) or (VI), resp.] with high enantioselectivities.